Catch-up growth in early treated patients with growth hormone deficiency. Dutch Growth Hormone Working Group. - Boersma, B (1995)
Catch-up growth of 26 children with growth hormone deficiency during four years of growth hormone treatment, which was started young (< 3 years), was compared with that of 16 children with coeliac disease on a gluten free diet. In children with growth hormone deficiency mean (SD) height SD score increased from -4.3 (1.8) to -1.9 (1.4) and in patients with coeliac disease from -1.8 (0.9) to -0.1 (0.8). Height SD score after four years correlated positively with injection frequency and height SD score at start of treatment in children with growth hormone deficiency. All patients with coeliac disease reached a height above -2 SD scores after four years, while the height of 26% of children with growth hormone deficiency on daily injections and of 86% of children on 2 or 4 injections/week was still below -2 SD scores. In patients with growth hormone deficiency on daily injections with an initial height SD score between -2 and -4 catch-up was similar to that of patients with coeliac disease with a comparable initial height deficit. Growth hormone deficient children with an initial height SD score < -4 did not reach full catch-up growth within four years. In conclusion, catch-up growth in early treated children with growth hormone deficiency over four years is adequate provided that daily injections are given and the initial height SD score is not less than -4.